CP-142 Antiretroviral therapy optimisation in multitreated hiv patients: clinical and pharmacoeconomic approach in the ecovir study. (25th February 2017) - Durand, L; Valantin, MA; Ktorza, N; Lenclume, L; Peytavin, G; Wirden, M; Costagliola, D; Assoumou, L; Katlama, C; Patrick, T
Abstract : Background: Some patients infected with multiresistant HIV receive lifelong antiretroviral (ARV) treatments. Long term drug effects on the patient and economic burden for society have to be weighed. These patients have a long virological history and a treatment optimisation strategy requires a multiparametric and individualised evaluation. Purpose: Evaluating the clinical and economic impact of a therapeutic optimisation strategy for patients receiving multitherapy. Material and methods: Eligible patients were receiving 4 ARV and had a viral load(VL) of <50 copies/mL for >12 months. A multidisciplinary expert team suggested a new optimised treatment with <3 ARV, based on analysis of drug resistance mutations, history of ARV treatments and drug–drug interactions. The first endpoint was the proportion of patients with VL <50copies/mL after 6 months. Economic impact was evaluated according to drug and laboratory costs (VL, CD4, drug level testing). Quality of life data were also collected for a cost–utility analysis. Results: Of the 4277 patients receiving HIV treatment, 146 were on >4 ARV drugs. 89 patient files were discussed with HIV experts, 82% treated with 4 ARV, 17% with 5 ARV and 1% with 6 ARV. Median age (min–max) was 58 years (33–85), HIV diagnostic period was 27 years (2–33), ARV treatment period was 22 (2–30) and number of treatment lines was 14 (2–32). To date, 71 (79.8%) patients have switched to tri- or bi-therapy (77.5% and 22.5%) and 56 (78.9%) have reached the first endpoint. Therapeutic optimisation leads to significant diminution of prescriptions for (non-)nucleoside reverse transcriptase inhibitors (−74%), protease inhibitors (−37%) and maraviroc (−48%). Only integrase inhibitors were prescribed more often after therapeutic optimisation (+6%, 77.5% of bi-therapies). The median monthly drug cost significantly decreased from €1746 to €1112 (−36%, Wilcoxon test) with annual savings of about €0.5M for this cohort. Cost savings remained significant even with the integration of laboratory costs (−26%). To date, virological suppression has been maintained in 93.0% of patients. Quality of life criteria will be analysed at the end of this ongoing study. Conclusion: Multi-therapies represent a minor part of the current strategies. Therapeutic individualised optimisation reduces the daily number of ARV and has a significant economic impact, despite additional costs due to the resulting follow-up of a treatment switch, to ensure virological success and tolerance of the new treatment. No conflict of interest